Optimalisasi sistem pemberdayaan wakaf produktif sebagai alternatif sumber ekonomi umat - Muh. Shaleh Suratmin (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
Wakaf is one of the main religious service which contains productive economic values but in reality thevalues haven’t fully been implemented. The most important factor of this is the lack of socialization and the minimum role of the government (Badan Wakaf Indonesia). The enactment of the new wakaf bill (UU No. 41/2004) which followed by Peraturan Pemerintah Nomor 42 Tahun 2006 has not effective yet. How to maximize waqf advantages for society empowerment? This is the focus of study. The result of study shows that wakaf is very important to be the source of capital for empowering umat’s economy. The way to understand (fiqh) wakaf must be reformulated. The maximization of productive wakaf needs proper public understanding and good management. That is why that the nadhir must fulfill moral, managerial, and entrepreneur qualifications. The writer conclude that only trough revitalizing the role of BWI and the public awareness, the new paradigm of waqf can be realized in Indonesia.